Project Management Methodology And Best Paractices To Manage Virtual Teams When Outsourcing It Functions - Singh, Jagdesh (2007)
Our research aims to understand, through literature study, what are the most successful It project management methodologies that exist today in large enterprises. From these methodologies, wehope to understand how to run the full lifecycle of an IT project.